Green Supply Chain Management Performance Measurement in Palembang Rubber Industry - Masayu Rosyidah; Anindita Rahmalia Putri (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
Rubber is one of the non oil-gas product from South Sumatera. However, several companies in this sector are not yet concerned with environmental aspects. Most companies have a profit-oriented goal regardless of environmental aspects especially waste management. The environmental aspect has not been integrated into the supply chain in practice so that its implementation has not been effective. Green supply chain management is a way to integrate it. Applications of green supply chain management in companies could help to minimize the impact of environmental pollution. However GSCM performance measurement has not been widely carried out in the rubber processing industry, especially those located in South Sumatra. So the aim of this research is to analyze the performance of GSCM using the green SCOR model. The results showed that the value of GSCM performance in PT. Sunan Rubber Palembang is categorized as average with a value of 64.03.